Etude Des Parametres Floraux De Quatre Varietes L’abricotier Dans La Region De Guedila (Biskra, Algerie) - Abdelaziz, Benaziza; Samiha, Makhloula (European Scientific Journal, ESJ, 2017)
In the Guedila region (Biskra, Algeria), fruit trees have become increasingly important in recent years, occupying enormous areas and important plant resources. Among these, apricot tree (Prunus armeniaca L.) or (Armeniaca vulgaris Lam.). Which is undergoing a notable development due to the good adaptation of this species to the regional pedoclimatic conditions which generate very satisfactory yields? This work allows the floral characterization of four varieties of apricot, most cultivated in this region. It is based mainly on the descriptor of the European union of production and plant breeding (UPOV, 2008) which allows varietal identification, their performances and the existing analogies between the varieties studied.